Identify spin property of relativistic electrons in fully relativistic laser fields. (23rd December 2021) - Li, X B; Gan, L F; Wang, J; Jiao, J L; Jin, S; Zhuo, H B; Zhou, C T; Zhu, S P; He, X T; Qiao, B
Abstract: A semiclassical method is developed to study the spin evolution of a relativistic electron in an fully relativistic laser pulse. Different from the previous classical method which is based on the direct generalization of nonrelativistic spin precession equation, we perform first-principle calculations on the mean values of various spin operators with respect to a relativistic electron wave packet. It is demonstrated, via theoretical derivation and numerical simulation, that although the Foldy–Wouthuysen operator merits the single-particle interpretation, its mean value obviously deviates from the result of the classical method, which sheds light on not only the understanding of relativistic spin itself but also broad related applications. To achieve a direct observation of such effect, a feasible experimental setup utilizing the asymmetric field of a single-cycle laser is proposed. In such geometry, the deviation is evidenced in the total change of spin which can be easily measured after the interaction.